Репродуктивне насильство: десубʼєктивація жінки в романі «Уражені» Ульріке Дрезнер - Микитюк, Ірина (Літературний процес: методологія, імена, тенденції, 2025)
This article offers an analysis of «Die Verwandelten» (2023), a novel by contemporary German author Ulrike Draesner, which, among other themes, portrays the traumatic experiences of women involved in the Nazi «Lebensborn e.V.» program — one of the least explored aspects of Hitler’s demographic policy. The study focuses on the phenomenon of reproductive violence as a form of state control over the female body, and, in this context, on the literary representation of trauma. Through a complex narrative structure that intertwines multiple temporal layers, Draesner’s novel illustrates the intergenerational transmission of traumatic experience and the mechanisms of its literary articulation. The article explores how the female body and the totalitarian ideological construction of motherhood are revealed as instruments of coercion and dehumanization. It also investigates how literature can function as a means of restoring the voices, subjectivity, and memory of victims. By employing the concepts of cultural memory, postmemory, and trauma theory, the article demonstrates how Draesner integrates complex ethical, historical, and bodily issues into the fabric of the narrative. «Die Verwandelten» is interpreted as an important contribution to contemporary German-language literature that not only reflects on a traumatic past but also expands the boundaries of representing female experience within the context of political violence.